Deletion of PRAK Mitigates the Mitochondria Function and Suppresses Insulin Signaling in C2C12 Myoblasts Exposed to High Glucose - Zhang, Ling; Wang, Jianguo; Zhao, Yu Tina; Dubielecka, Patrycja; Qin, Gangjian; Zhuang, Shougang; Chin, Eugene Y; Liu, Paul Y; Zhao, Ting C (Frontiers in Pharmacology, 2021)
Background: p38 regulated/activated protein kinase (PRAK) plays a crucial role in modulating cell death and survival. However, the role of PRAK in the regulation of metabolic stress remains unclear. We examined the effects of PRAK on cell survival and mitochondrial function in C2C12 myoblasts in response to high glucose stresses. Methods: PRAK of C2C12 myoblasts was knocked out by using CRISPR/Cas-9 genome editing technology. Both wild type and PRAK-/- C2C12 cells were exposed to high glucose at the concentration of 30 mmol/L to induce metabolic stress. The effect of irisin, an adipomyokine, on both wild type and PRAK-/- cells was determined to explore its relationship with RPAK. Cell viability, ATP product, glucose uptake, mitochondrial damage, and insulin signaling were assessed. Results: PRAK knockout decreased C2C12 viability in response to high glucose stress as evident by MTT assay in association with the reduction of ATP and glucose uptake. PRAK knockout enhanced apoptosis of C2C12 myoblasts in response to high glucose, consistent with an impairment in mitochondrial function, by decreasing mitochondrial membrane potential. PRAK knockout induced impairment of mitochondrial and cell damage were rescued by irisin. PRAK knockout caused decrease in phosphorylated PI3 kinase at Tyr 485, IRS-1 and AMPKα and but did not affect non-phosphorylated PI3 kinase, IRS-1 and AMPKα signaling. High glucose caused the further reduction of phosphorylated PI3 kinase, IRS-1 and AMPKα. Irisin treatment preserved phosphorylated PI3 kinase, IRS-1by rescuing PRAK in high glucose treatment. Conclusion: Our finding indicates a pivotal role of PRAK in preserving cellular survival, mitochondrial function, and high glucose stress.